Changing perspectives of time in HCI - Lindley, Siân; Vaara, Elsa; Ferreira, Pedro; Simbelis, Vygandas; Corish, Bob and (CHI 2013 Extended Abstracts, 2013)
The aim of this workshop is to unpack different ways of thinking about time, drawing a distinction between time as experienced, and time as counted by a ticking clock or measured by a computer algorithm. The concept of time is often taken for granted within HCI, yet high-lighting the assumptions that underpin it could provide a resource for research and innovation. In this extended abstract, we illustrate how this is so.